Pengaruh Coping Stress Dengan Subjective Well-Being Pada Wanita Dewasa Awal Yang Belum Menikah - Adetya, Sandra; Manurung, Gabriel Yohanes (Jurnal Kajian Ilmiah, 2022)
Aims of this studi is to determine whether coping stress has an effect on subjective well-being in unmarried women of early adulthood. Hypothesis used in this study is that coping stress can have a positive effect on the subjective well-being of unmarried women of early adulthood. The subjects in this study were unmarried early adult women with a total of 107 respondents. This study uses two measuring tools, namely the Coping Stress scale and also the Subjective Well-being scale, with a reliability coefficient value of 0.756. data analysis in this study use a simple regression technique that may use software SPSS 23 for windows. The testing of hypothesis result shown that coping stress can provide significant effect on subjective well-being with a value of F = 57,577 and a value of p = 0.000 (p <0.001). The result of the R square value is 56.3%, while the rest 43.7% is be affected by other factors.